Cathepsin G and Its Role in Inflammation and Autoimmune Diseases - Siming GAO; Honglin ZHU; Xiaoxia ZUO; Hui LUO (Archives of Rheumatology, 2018)
Cathepsin G belongs to the neutrophil serine proteases family, known for its function in killing pathogens. Studies over the past several years indicate that cathepsin G has important effects on inflammation and immune reaction, and may be a key factor in the pathogenesis of some autoimmune diseases. In this article, we discuss the roles of cathepsin G in inflammation, immune reaction, and autoimmune diseases. To our knowledge, this is the first study providing important information about cathepsin G in the pathogenesis of autoimmune diseases and suggesting that cathepsin G may be a new biomarker or treatment target.